2021
DOI: 10.1109/access.2021.3107353
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Road Boundary for Intelligent Vehicles Based on DeepLabV3+ Architecture

Abstract: Road boundary estimation is an essential task for autonomous vehicles and intelligent driving assistants. It is considerably straightforward to attain the task when roads are marked properly with indicators. However, estimating road boundary reliably without prior knowledge of the road, such as road markings, is extremely difficult. This paper proposes a method to estimate road boundaries in different environments with deep learning-based semantic segmentation, and without any predefined road markings. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 40 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Inspired by [ 44 ] and its work on road boundary estimation, we employed a reduced ResNet50 [ 42 ] network (without the fourth block) for feature extraction. We found that using a backbone model with a small depth yields better results with our dataset.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Inspired by [ 44 ] and its work on road boundary estimation, we employed a reduced ResNet50 [ 42 ] network (without the fourth block) for feature extraction. We found that using a backbone model with a small depth yields better results with our dataset.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Inspired by [42] and its works on road boundaries estimation, we employ reduced ResNet50 [9] network (without the 4th block) for features extraction. We have found that using a backbone model with a small depth yields better results with our dataset.…”
Section: Backbone and Features Extractionmentioning
confidence: 99%
“…After each convolution layer, a ReLu activation function exists to ensure non-linearity, which avoids acting like a single layer for sequential layers. The last layer in each block involves a 2×2 max-pooling that decreases the spatial resolution of feature maps (Das, Fime, Siddique, & Hashem, 2021). The filters of each convolution in the blocks are 64, 128, 256, 512, and 512.…”
Section: Vgg-16 As Backbonementioning
confidence: 99%
“…VGG-19 architecture contains five blocks with 16 convolution layers and has a small receptive field of 3x3 (Das et al, 2021). Each convolution layer follows a ReLu activation function, while a max-pooling is used in the last convolution layer of each block.…”
Section: Vgg-19 As Backbonementioning
confidence: 99%